KUALITAS PELAYANAN PRAMUSAJI RESTORAN SIGNATURE HOTEL INDONESIA KEMPINSKI JAKARTA: SOP, pelayanan, pramusaji - heri sutardi; I Gusti Ngurah Juan Brian (Akademi Pariwisata NHI Bandung, 2023)
This research is to find out the quality of waitress service at the Signature Hotel Indonesia Kempinski Jakarta Restaurant and to find out the problems that can be encountered when serving visitors at the Signature Jakarta Hotel Indonesia Kempinski Jakarta. This research was conducted at the Signature Hotel Indonesia Kempinski Jakarta Restaurant. The research method used is a method that is descriptive analysis using continuum analysis. The results of this study are: The following is an analysis of guest responses regarding the procedural dimension: 1) The speed aspect of getting results is Enough with an average value of 90 at Signature Jakarta Hotel Indonesia Kempinski Jakarta. 2) The communication aspect has not good results with an average value of 68, guests think that communication between waiters is not well established. 3) The service flow aspect gets unfavorable results with an average value of 65, so from these results guests assume that the waitress service flow is not good. 4) The anticipation aspect gets unfavorable results with an average value of 60, therefore the guests assume The waiter's anticipation of the needs and desires of guests is not fulfilled. 5) The reciprocal aspect of getting results is sufficient with an average value of 81, therefore guests assume that the waiter provides a place for guests to give feedback. 6) The Accommodation Aspect gets Enough results with an average value of 78, therefore the guests think that the accommodation system is running quite well. 7) Coordination and supervision aspects get Enough results with an average score of 77, therefore the guests think that the supervision from superiors to subordinates is going quite well. 519. The following is an analysis of guest responses regarding the conviviality dimension: 1) The Helpful aspect gets a Not Good result with an average value of 64, so from these results the guests assume that the waiter's ability to provide full assistance such as escorting guests to the table, bringing guests' goods , and others are considered less satisfactory. 2) The Body Language aspect gets a Bad score with an average score of 69, guests think the facial expressions and eye contact of the waitress are not friendly. 3) The Tone of Voice aspect gets Bad results with an average value of 65, so from these results the guests judge the waiter's tone of voice when talking to guests is not audible. 4) The Selling Skill aspect did not get good results with an average value of 73, so from these results the guests thought that the waiter's ability to sell a product was assessed as lacking by the guests. 5) The naming name aspect gets a bad result with an average value of 73, therefore the guests think that the waiter doesn't know the guest well. 6) The guidance aspect gets Unfavorable results with an average value of 66, so from these results the guests think that the waiter is not good at providing hotel knowledge. 7) The tactile aspect gets a Bad score with an average score of 70, so from these results the guests think that the wise attitude of the waitress is considered to be lacking in maintaining attitudes in the work environment. 8) The Attentiveness aspect gets a Not Good result with an average value of 64, so from these results the guests think the attention of the waiter towards the guest is considered to be insufficient to meet guest satisfaction. 9) The Problem Solving aspect has not good results with an average score of 68. Guests think that the ability of waiters to solve problems is considered lacking. This is because the waiter is not good enough because he is still afraid and doubtful in making decisions. , in the implementation of the coviviality dimension as a whole the assessment obtained a Not Good score with an average score of 609. Conclusion: From the above results of the questionnaire analysis, it can be concluded that the implementation of the procedural dimension aspect at the Signature Hotel Indonesia Kempinski Jakarta Restaurant is sufficient, but there are many points that must be corrected in order to support progress from the procedural aspect. Meanwhile, from the results of the analysis above in the questionnaire, it can be concluded that the implementation of the conviviality dimension at the Signature Hotel Indonesia Kempinski Jakarta Restaurant is not good at meeting guest needs. in serving guests because of. Therefore, the aspect of conviviality at the Signature Hotel Indonesia Kempinski Jakarta Restaurant must be improved Keywords: SOP, services, waiter